Assessing infertility-related stress: the factor structure of the Fertility Problem Inventory in Italian couples undergoing infertility treatment. (June 2015) - Donarelli, Zaira; Gullo, Salvatore; Lo Coco, Gianluca; Marino, Angelo; Scaglione, Piero; Volpes, Aldo; Allegra, Adolfo
Abstract: The factor structure of the Fertility Problem Inventory (FPI) and its invariance across gender were examined in Italian couples undergoing infertility treatment. About 1000 subjects (both partners of 500 couples) completed two questionnaires prior to commencing infertility treatment at a private Clinic in Palermo, Italy. Confirmatory Factor Analysis demonstrated that the original factor structure of the FPI was partially confirmed. Two correlated factors ( Infertility Life Domains and Importance of Parenthood ) were obtained via a post hoc Exploratory Factor Analysis . Finally, the invariance of this factor structure across gender was confirmed. The study supported the relevance of two interrelated factors specific to infertility stress which could help clinicians to focus on the core infertility-related stress domains of infertile couples.